ATRAKSI DESTINASI WISATA DALAM MENDUKUNG TERBENTUKNYA DESA WISATA BANYU URIP KEDAMEAN GRESIK - Mohammad Insan Romadhan; Mulyanto Nugroho (Universitas Merdeka Malang, 2021)
Banyu Urip Village, which is famous for its adenium plants, is a place that is visited by many people. Unfortunately, this potential has not been able to make Banyu Urip Village a Tourism Village. So it is necessary to do a mapping related to the carrying capacity that can support the formation of a Tourism Village. One of them is by mapping the tourist destination attractions owned by Banyu Urip Village. The tourist destination attractions that will be studied use Middleton's tourist attractions which involve natural, social, cultural and artificial attractions. The research approach uses qualitative with descriptive research type by observing directly the findings in the field accompanied by in-depth interviews. The informants in this study were representatives from the association of ornamental plant centers, the head of youth organizations and several people of Banyu Urip Village. The results showed that of the four tourist attractions, Banyu Urip Village has natural attractions in the form of flora, high and lowlands and trees. Cultural attractions that have a lot of myths circulating as well as attractions made by ornamental plant centers. Where these attractions can be used as a carrying capacity in forming a Tourism Village. Coupled with combining various kinds of existing attractions such as natural flora attractions with artificial attractions in the form of shopping places (ornamental plant centers). Natural attractions of highlands and trees with cultural attractions that can be used as new tourist objects, namely mystical tourism.